Figurative Language Analysis in a Poetry Entitled ‘Life Does Not Frighten Me’, ‘Equality’, and ‘Alona’ by Maya Angelou - Arini Hidayah; Tiara Purba (Universitas Musamus Merauke, 2021)
This research used a descriptive qualitative method used to analyze data. Figurative language was analyzed based on theories from Perrine which involves: simile, metaphor, personification, apostrophe, synecdoche, metonymy, symbol, allegory, paradox, hyperbole, understatement, and irony. This research purposes to find out the types of figurative language, to know the most dominant and the submissive figurative language and to reveal the purposes meaning of figurative language used in poetry by Maya Angelou with title Life Does Not Frighten Me, Equality, and Alone. The data source from poetry collection by Maya Angelou with titled ‘Life Does Not Frighten Me’, ‘Equality’, and ‘Alone’. The techniques of collecting data used by the researcher are documentation via internet. The data was analyzed through four stages: a) Coding, b) Data Reduction, c) Data Display, and d) Conclusion. The researchers concluded the result of this research were 39 poem lyric that containing 11 figurative languages types. The dominant figurative language types is Hyperbole and the submissive figurative language is Paradox and Irony. The researchers found 11 purposes meaning of figurative language that can reveal new predictable to force readers to imagine what writer wants to express.